PELAKSANAAN LELANG BARANG HASIL SITA PAJAK MELALUI KANTOR PELAYANAN PAJAK PRATAMA SECARA ONLINE DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG KOTA MEDAN - PUTERI INTAN SUHAILA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. Sutiarnoto, SH, MHum3. Dr. Affila, SH, MHum Along with the development of technology, the concept of an auction also developed. The auction that used to be conducted orally in public, at present it can be done by online. The research problems found in the study is how the fulfillment onthe principle of legal certainty is in an auction of items from confiscated taxes through the KPP Pratama byonline goods, how legal protection is for the auction participants of the goods from the confiscated in taxes online through KPP Pratama at KPKNL Medan provides legal certinty for the auction participants.Legal certainty in the mechanism of implementation of the online auction is still not entirely fulfilledbecause there are some short comings in the implementation of online auctions, becauseinjustice arises in its implementation.Keyword: The Confiscation Tax Items; auction; Online Auctions.